SNAKEBITE ACCIDENTS IN THE AMAZON AND THEIR LOCAL COMPLICATIONS: TISSUE NECROSIS ASSOCIATED WITH PREDOMINANT SPECIES IN THE STATE OF AMAZONAS - Dias, Thaís da Costa; Ditta, Caty Esbelana Urrego; Lavor, Laisa Divina Vieira; Nunes, Kezia de Souza; Ferreira, Kessia Cibele Machado; Freitas, Paula Cristine da Silva; da Costa, Walter Oliveira; Gonçalves, Dimas Melo (Seven Editora, 2026)
Snakebite accidents represent a significant public health issue, particularly in the Amazon region, where environmental and occupational factors, along with high biodiversity, increase human exposure to venomous snakes. In this context, the genus Bothrops stands out as the main cause of envenomation, often associated with severe local complications such as tissue necrosis. This study aimed to analyze snakebite accidents in the Amazon and their local complications, with emphasis on tissue necrosis associated with predominant species in the state of Amazonas. This is a qualitative, exploratory, and descriptive study conducted through a literature review of scientific articles published between 2021 and 2026, selected from relevant health science databases. The findings indicate that Bothrops atrox is the primary species involved in snakebite cases in the region, responsible for intense local clinical manifestations such as edema, pain, hemorrhage, and tissue necrosis. Furthermore, the severity of complications is directly related to the time to medical care and the amount of venom injected, potentially leading to permanent sequelae and significant impacts on patients’ quality of life. It is concluded that snakebite accidents in the Amazon constitute a complex phenomenon with important clinical and social implications, highlighting the need for effective strategies for prevention, early diagnosis, and appropriate treatment.